Cuproptosis-related lncRNAs and genes: Potential markers for glioblastoma prognosis and treatment. - Yajia Chen; Jingxian Zhang; Weiqian Zheng; Hongwu Xu (PLoS ONE)
Despite the availability of various treatment options, glioblastoma (GBM) remains an extremely aggressive form of glioma with a poor prognosis. In recent studies, regulatory cell death (RCD) has been identified as an effective mechanism to suppress glioma. Cuproptosis, caused by intracellular copper, is a novel RCD process that affects chemotherapy efficacy and glioma progression; however, the precise function of cuproptosis-related lncRNAs (CRLs) and cuproptosis-related genes (CRGs) in GBM remains uncertain. To determine whether CRLs and CRGs have prognostic significance, a GBM cohort in TCGA to build a novel cuproptosis-related risk model. Two high-risk CRLs (AC091182.2, AC005229.4) and their co-expression CRGs (LIPT2, GLS) were identified and verified to constitute an independent prognostic indicator of GBM. RT-qPCR analysis confirmed that the high-risk CRLs and CRGs were highly expressed in GBM cells compared to normal astrocytes. By constructing a mouse GBM model, high-risk CRLs and CRGs were found to be expressed at higher levels in tumor tissues. Furthermore, to verify whether these CRLs and CRGs are associated with GBM cuproptosis, cuproptosis cell models were constucted in GBM cell lines and astrocyte by using Elesclomol and CuCl2. It was found that the expression of high-risk CRLs and CRGs was decreased upon cuproptosis-induced in GBM cells. Interestingly, normal astrocytes were less sensitive than GBM cells to cuproptosis-inducing drugs, and the effects of the drugs on the expression of the CRLs and CRGs in normal astrocytes were opposite to that of in GBM cells. In conclusion, by constructing a novel cuproptosis-related risk model, two high-risk CRLs and CRGs were identified. Their specific pointing to GBM has been demonstrated through a variety of experiments. These CRLs and CRGs might serve as prognostic markers and indicators for GBM and provide theoretical support for future GBM treatment.